Pengaruh Negative eWOM: Studi Empiris pada Konsumen Maskapai Penerbangan Lion Air - Kurniawati Putri, Rini; Bharata, Wira (Universitas Negeri Padang, 2024)
This research objectives to determine the influence of negative ewom on brand image and brand trust and its impact on interest ini buying Lion Air airline tickets. This research uses descriptive quantitative research methods. Sampling in this research used a non-probability sampling method, namely purposive sampling by distributing questionnaires as a data collectiom method. The samples researched in this study were 120 respondents who used airline. Based on the results of research testing, it shows that: 1) Negative ewom has a negative effect on the brand image of Lion Air airline 2) Negative ewom has a negative effect on the brand trust of Lion Air airline 3) Brand image has a positive effect on interest in buying Lion Air airline tickets 4) Brand trust has a positive effect on interest in buying Lion Air airline tickets 5) Negative ewom has a negative effect on interest in buying Lion Air airline tickets